Circadian light therapy and light dose for depressed young people: a systematic review and meta-analysis - Chen, Ranpeng; Yan, Yonghong; Cheng, Xiang (Frontiers in Public Health, 2024)
Background: Although positive clinical outcomes for depression symptom reduction by circadian stimulus of light therapy (LT) have shown empirically, there exist inconclusive results and skepticism about the efficacy of light therapy, accompanied with dosing confusion. The study aims to provide guidance by quantifying light as a stimulus for the circadian system and build dose-response relationship with maladies reduction among adolescent and young adults (AYAs), therefore providing quantified reference for light pattern and neural response vital in neuropsychological mechanism of light intervention, as well as to provide guidance for clinical application. Methods: The latest quantitative model of CLA (circadian light) and CSt,f (circadian stimulus) was adopted to quantify light dose for circadian phototransduction in youth depression related light therapy. Articles published up to 2023 through Web of Science, Cochrane Library, Medline (OVID), CINAHL, APA PsycINFO, Embase and Scholars were retrieved. Meta-analysis of total 31 articles (1031 subjects) were performed using mainly Stata17.0, CMA3.0 (comprehensive meta-analysis version 3.0) software and Python 3.9 platform for light therapy efficacy comparison as well as doseresponse quantification. Results: Under various circadian stimulus conditions (0.1